MOTIVASI DAN STRES KERJA SERTA PENGARUHNYA TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI DI PT DELTA JAYA MAS - Hariyanti, Via; Wibowo, Tony Susilo (Fakultas Ekonomi Universitas PGRI Adi Buana, 2015)
This research aims to know the influence of motivation and stress of work against employee productivity part production in PT. Delta Jaya Mas. From the results of research that has been done by using questionnaires and documentation against 95 respondents taken with random sampling techniques. Motivation and job stress have an influence partially against work productivity of employees part of the production of PT. Delta Jaya Mas, accepted and proven the truth by using test – t obtained t count variable = value with 3,102 motivation sig. 0.003 so (0.003 < 0.05) and work stress =-value sig 3,376. be 0.001 (0.001 < 0.05). Motivation and job stress have an influence employee to productivity the simultaneous production of PT. Delta Jaya Mas, accepted and proven the truth by using the F test obtained F count = 6,000 value of sig. = 0,004 (0,004  0.05). The correlation coefficient (R) of 0,340 shows that there is a less powerful relationship between work stress and motivation to productivity. The coefficient of determination (R square) of 0.115. This figure shows that motivation and stress of work provide variations or capable of contributing to a variable productivity amounted to 11.5%, while the remaining registration 88.5% are caused by other variables that are not included in the study.